The Experience of Islamic Art on the Margins of Islam: By Irene A. Bierman, ed. (Reading, UK: Ithaca Press in association with the Gustav E. von Grunebaum Center for Near Eastern Studies, 2005. 172 pages.) (American Journal of Islam and Society, 2007)
This volume is the fifteenth publication in the Giorgio Levi Della Vida ConferencePapers series, each of which contains the lecture presented by therecipient of the Giorgio Levi Della Vida Award for excellence in Islamicstudies along with contributions by other scholars dedicated to a specialtopic. For the first time ever, in 1996 the award was presented to an art historian,Oleg Grabar, who chose “The Experience of Islamic Art on theMargins of Islam” as the theme of the fifteenth conference. The crossing of boundaries by artifacts, decorative elements, or figuralsubjects from one cultural hemisphere into another, as well as the perceptionof the “inherited” monuments of other cultures, is a broad and still largelyunexplored field. While studies following the wandering of motifs are quitenumerous, the reasons for their selection and tacit integration into new contexts,along with their reshaping and revaluation, are not dealt with veryoften. Each of the five articles directs our attention to a particular border areaof Islamic culture during a particular period, ranging from the Middle Agesto the present. Each contribution also approaches the question of how(regardless of the way) acquired Islamic objects and monuments weredealt with from a specific angle. The result is a small and very diverse collectionof experiences that surely does not offer an overview of all responsesto Islamic art. However, it convincingly demonstrates how revealing researchon the cultural margins can be ...